2022
DOI: 10.1080/08897077.2021.2010260
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Perceived Clinical Knowledge Uptake among Health Profession Students and Licensed Clinicians Receiving Buprenorphine Waiver Training in Oregon

Abstract: Background: Addressing the opioid crisis requires an understanding of how to train both health professional students and practicing clinicians on medications for opioid use disorder (mOUD). We designed a robust evaluation instrument to assess the impact of training on perceived clinical knowledge in these different categories of learners. Methods: We enrolled 3rd and 4th year medical, physician assistant (PA), and nurse practitioner (NP) students, as well as practicing PAs, NPs, and physicians to undertake the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In fact, in 2018, the Substance Abuse and Mental Health Services Administration started to provide funding for medical schools willing to adjust their curriculum to fulfill waiver training requirements, but only one school has done so [ 10 ]. Some recent pilot studies in the United States have shown that integrating waiver training for medical students does increase knowledge, interest, and confidence in diagnosing and treating OUD [ 16 , 17 ], and calls attention to the need for a standardized, nationwide course, as there is currently none. A key advantage of GW courses is that even though the requirements for buprenorphine prescription have been relaxed, GW can provide mentorship and education in a brief, free, virtual, and interactive setting that boosts confidence and arms clinicians with the tools they need to effectively use their X waiver.…”
mentioning
confidence: 99%
“…In fact, in 2018, the Substance Abuse and Mental Health Services Administration started to provide funding for medical schools willing to adjust their curriculum to fulfill waiver training requirements, but only one school has done so [ 10 ]. Some recent pilot studies in the United States have shown that integrating waiver training for medical students does increase knowledge, interest, and confidence in diagnosing and treating OUD [ 16 , 17 ], and calls attention to the need for a standardized, nationwide course, as there is currently none. A key advantage of GW courses is that even though the requirements for buprenorphine prescription have been relaxed, GW can provide mentorship and education in a brief, free, virtual, and interactive setting that boosts confidence and arms clinicians with the tools they need to effectively use their X waiver.…”
mentioning
confidence: 99%